Position Paper Number 3 for the Workshop “Towards Criteria of Sustainability and Social Meaningfulness in Development“: The emerging ecology of genetic, digital and cultural (including non-Western) information environments - Susantha Goonatilake (tripleC: Communication, Capitalism & Critique)
Position Paper Number 3 for the Workshop “Towards Criteria of Sustainability and Social Meaningfulness in Development“: The emerging ecology of genetic, digital and cultural (including non-Western) information environments